Characteristics and Antioxidant Activity of Limau Kuit Peel (Citrus hystrix) Extract with Variation of Extraction Solvent - Rizki, Muhammad Ikhwan; Agustina, Ni Kadek Ayu; Sari , Anna Khumaira; Rahmatullah, Satrio Wibowo; Isnani, Nazhipah (Medical Laboratory Technology Journal, 2025)
Limau kuit (Citrus hystrix) has been traditionally utilized for its therapeutic properties, particularly the antioxidant potential of its peel. Extraction is preferred for medicinal use, with solvent selection playing a critical role in determining the yield and concentration of bioactive compounds. This study aimed to assess the characteristics and antioxidant activity (IC₅₀ value) of Limau Kuit peel extract extracted with three different solvents. The research methods, starting with sample preparation, were carried out by drying Limau Kuit peel, then extraction using three different solvents: distilled water, ethanol 70%, and ethanol 96%. Extraction with distilled water solvent used the infusion method, while the ethanol solvent used the maceration method. The third extract was then characterized based on the parameters of percent yield, organoleptic testing, phytochemical screening, chromatography profile, and determination of total flavonoid levels. Antioxidant activity testing on the third extract using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. The study results showed that the third extract had the same shape, color, aroma, taste, and compound content: flavonoids, phenolics, alkaloids, and terpenoids. The results of thin-layer chromatography also showed no difference in the third extract. The characteristic differences were found in the parameters of percent yield and total flavonoid content.  The highest total flavonoid content of Limau Kuit (Citrus hystrix) peel extract was obtained using 70% ethanol (11.47% w/w), followed by 96% ethanol (6.39% w/w), and distilled water (2.82% w/w). Antioxidant activity, evaluated using the IC₅₀ value as the parameter, showed that the 70% ethanol extract exhibited the strongest activity (21.26 ppm, very strong), followed by the 96% ethanol extract (31.87 ppm, very strong), and distilled water extract (70.91 ppm, strong). This study concludes that 70% ethanol is the most effective solvent for extracting antioxidant-rich compounds from Limau Kuit peel, supporting its potential use in herbal formulations.